Productive characteristics of the grass Digitaria umfolozi subjected to defoliation frequencies - Araujo, Helber Rodrigues; De Albuquerque Rangel, José Henrique; Fagundes, Jailson Lara; Muniz, Evandro Neves; De Oliveira Santos, Daniel; Neto, José Adelson Santana; Filho, Edivilson Silva Castro [UNESP]; De Arruda Santos, Gladston Rafael (Universidade Estadual de Londrina, 2017)
An experiment was carried out to evaluate the dry matter production, total dry matter availability, daily dry matter accumulation rate, light interception, leaf area index, daily accumulation rate and dry matter availability of the morphological components (leaf blades, stems + sheaths and dead material), leaf/stem ratio, crude protein, neutral detergent fibre and acid detergent fibre of Faixa-Branca grass under seven defoliation frequencies (14, 21, 28, 35, 42, 49, and 56 days). Longer defoliation frequencies reduced the percentage of leaf blades and increased the percentage of stems + sheaths. The defoliation frequency positively influenced the availability of leaf blades, stems + sheaths, dead material and total dry matter. In the range of 42 days of defoliation, light interception reached 95%. At frequencies of 14 and 21 days of defoliation, the crude protein content of the leaves was above 20%. The highest utilization efficiency of Faixa-Branca grass is achieved when the forage is managed with cutting intervals of 40 to 46 days. Higher defoliation frequencies positively contribute to the increase in the number of total white band grass leaves and higher crude protein content of the leaf blades and stems + sheaths.
Keywords: Crude protein; Digitaria umfolozi; Forage production; Light interception